A checklist of cercariae (Trematoda: Digenea) in molluscs from Brazil - Pinto, Hudson Alves; de Melo, Alan Lane (Zootaxa, 2013)
A checklist of digenetic trematodes found in molluscs from Brazil is presented based on 127 scientific articles published after a century of studies. To date 23 families, 35 genera and 46 species of trematodes were identified infecting 25 species of molluscs in the country. Another 36 species described in the collective-group Cercaria were found in 15 species of mol-luscs and have not yet been associated with the respective adult parasites. Larvae found in 20 species of molluscs and grouped into 10 cercarian types are also listed.